Analysis of referrals of cancer patients to a Psycho-Oncology - Arrillaga Arizaga, Maite; Uranga Garciarena, Elena; Anton Mas, Cristina; Reguera Lago, Paula; Urreta Barallobre, Iratxe (Psicooncología, 2025)
Objective: The study analyzed the referral process to psycho-oncology services for cancer patients, with three main objectives: 1) to examine referral patterns across departments, 2) to evaluate the use of emotional (VAS) and social (Gijón) screening scales, and 3) to describe the interventions provided. The study aimed to identify gaps between the psychosocial needs reported in the literature and actual clinical practice. Methods: A retrospective study was conducted with 262 patients referred to the Psycho-Oncology Unit (UPSO) of a university hospital in 2022. Sociodemographic variables (age, sex, family situation), clinical variables (cancer type and stage), and referral-related variables (referring department and professional) were analyzed. The VAS (≥5) and Gijón (≥7) scales were used as screening criteria. Data were analyzed using STATA 18 with descriptive statistics. Results: Of the patients, 70% were women (mean age: 58 years), and 40% had breast cancer. Medical Oncology (66%) and the Breast Unit (20%) accounted for the majority of referrals, although only 1–1.5% of their consultations led to referrals. The VAS scale, applied in 49% of cases, detected distress in 68% of patients (≥5), while the Gijón scale, used in 67% of cases, identified only 11 cases (≥7). In 44% of cases, referrals did not adhere to standardized protocols. Of the referred patients, 92% received care (50% in a single session), with physicians initiating 81% of referrals. Conclusions: The study reveals underuse of validated screening tools, particularly the Gijón scale, variability in referral rates across departments, frequent reliance on non-standardized clinical criteria, and opportunities to improve screening through unified protocols and greater involvement of nursing staff. These findings highlight the need to enhance early detection of emotional distress in oncology settings.
Keywords: Psycho-oncology; emotional distress; clinical referral; distress thermometer; social vulnerability; psychological screening; comprehensive care; medical oncology